Realistic Ambient Occlusion In Real-Time - Survey of the AOV algorithm and propositions for improvements - Carlsson, Joakim (My University, 2010)
Ambient Occlusion is an area that has seen increased activity in the last few years and is an important aspect of reality in 3D-graphics. Rough approximation algorithms that are fast enough to be used in real games have appeared, but realistic solutions still have a way to go. This thesis covers an evaluation of the recently published Ambient Occlusion Volumes algorithm and presents various attempts of similar approaches to increase the algorithm performance. While no major breakthrough were made, it presents some new ideas and further examines some of those presented in the original paper. The algorithm is currently not fit for real-time rendered ambient occlusion except for applications dedicated to that purpose, but this might change in the near future, as it relies heavily upon the GPU which is a fast advancing field of technology. Kontaktskuggor är ett område som har sett ett ökat intresse de senaste åren. Grova approximeringsalgoritmer har dykt upp, men verklighetstrogna lösningar är inte riktigt där än. Denna rapport presenterar en undersökning av den nyligen presenterade algoritmen Ambient Occlusion Volumes. Den går även igenom ett flertal försök med liknande algoritmer i syftet att öka prestanda vid körning. Inga större genombrott har gjorts, men den presenterar ett antal nya idéer och går även in djupare på vissa områden än originalrapporten. Algoritmen är ännu för långsam för att användas till att rendera kontaktskuggor i realtid annat än i program som inte behöver övrig tillgång till grafikkortet. Detta kan emellertid komma att ändras inom en snar framtid då grafikkortsteknologin går starkt framåt.
Keywords: Datorteknik; Computer Engineering